Rare Variant Double-Layered Lateral Meniscus Detected During Arthroscopy in a Young Gymnast After a Hyperextension Knee Injury: A Case Report. Issue 3 (21st July 2020) - Looney, Austin M.; Ferris, William J.; West, Robin V.
Abstract : Case: A 15-year-old high-level gymnast sustained a hyperextension knee injury and was diagnosed with a lateral meniscus tear on advanced imaging. During arthroscopy, a redundant meniscus was encountered overlying an otherwise normal, intact lateral meniscus, consistent with a double-layer lateral meniscus. The redundant meniscus was resected, and the patient was able to return to gymnastics at her previous high level of competition. Conclusions: Abnormalities of the lateral meniscus may be poorly characterized or undetected on preoperative imaging studies. When the decision is made to proceed with surgery, a vigilant diagnostic arthroscopic examination can facilitate the detection and treatment of unanticipated pathology.